Proceedings of the Ocean Drilling Program 1992
DOI: 10.2973/odp.proc.sr.127128-1.184.1992
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Biomass and Activity in the Deep Sediment Layers of the Japan Sea, Hole 798B

Abstract: Sediment whole-round cores from a dedicated hole (798B) were obtained for detailed microbiological analysis, down to 518 m below the seafloor (mbsf) These sediments have characteristic bacterial profiles in the top 6 mbsf, with high but rapidly decreasing bacterial populations (total and dividing bacteria, and concentrations of different types of viable heterotrophic bacteria) and potential bacterial activities. Rates of thymidine incorporation into bacterial DNA and anaerobic sulfate reduction are high in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…A similar pattern is observed in the Santa Barbara Basin, where foraminifera are observed only to depths of 3 to 4 centimeters (Bernhard & Reimers, 1991), but bacteria have been observed to depths of 70 meters (Cragg et al, 1995). Based on an increasing number of observations of deep bacterial biomass at depths of hundreds of meters in marine sediments (e.g., Cragg et al, 1990;Cragg et al, 1992;Getliff et al, 1992;Parkes et aI., 1994), it is likely that bacteria exist at depths greater than 70 meters in the Santa Barbara Basin, as well.…”
Section: Study Site: the Central Santa Barbara Basinmentioning
confidence: 73%
“…A similar pattern is observed in the Santa Barbara Basin, where foraminifera are observed only to depths of 3 to 4 centimeters (Bernhard & Reimers, 1991), but bacteria have been observed to depths of 70 meters (Cragg et al, 1995). Based on an increasing number of observations of deep bacterial biomass at depths of hundreds of meters in marine sediments (e.g., Cragg et al, 1990;Cragg et al, 1992;Getliff et al, 1992;Parkes et aI., 1994), it is likely that bacteria exist at depths greater than 70 meters in the Santa Barbara Basin, as well.…”
Section: Study Site: the Central Santa Barbara Basinmentioning
confidence: 73%
“…2). This relationship has been commonly observed in Pacific Ocean sites Cragg et al, 1992;1995a, 1995bCragg and Parkes, 1994;Cragg and Kemp, 1995). Between 70 mbsf and the last sample at 108 mbsf, DDC were detected only once at 89 mbsf.…”
Section: Site 934mentioning
confidence: 81%
“…Recent Ocean Drilling Program (ODP) research on marine sediments (Whelan et al, 1986;Tarafa et al, 1987;Parkes et al, 1990Parkes et al, , 1994Cragg and Parkes, 1994;Cragg and Kemp, 1995;Cragg et al, 1990Cragg et al, , 1992Cragg et al, , 1995aCragg et al, , 1995b has confirmed the presence of a deep bacterial biosphere in marine sediments. Previously, this had only been predicted from the extensive amount of indirect geochemical evidence, that is, chemical changes in pore water, gas production, kerogen modification, concretion formation, and isotopic evidence (Krumbein, 1983;Suess and Whiticar, 1989;Kvenvolden and Kastner, 1990;Kastner et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…primarily by microscopic counts of cells stained with fluorescent DNA dyes were over 10 6 cells/cm 3 at depths exceeding 500 m below the sediment surface (Cragg, Wimpenny et al 1990;Cragg, Parkes et al 1992;Cragg 1994;Cragg and Parkes 1994;Parkes, Cragg et al 1994;Cragg, Parkes et al 1996;Wellsbury, Goodman et al 1997;Cragg, Law et al 1999;Parkes, Cragg et al 2000). In addition, other evidence exists that a high biomass of microbial life occurs deep within sediments and that these populations are active including 1) the presence of high molecular weight DNA that can be amplified using molecular techniques (Rochelle, Cragg et al 1994;Bidle, Kastner et al 1999;Li, Kato et al 1999;Vetriani, Jannasch et al 1999;Lanoil, Sassen et al 2001;LopezGarcia, LopezLopez et al 2001;Marchesi, Weightman et al 2001); 2) rapid growth of bacteria in mixed cultures (Getliff, Fry et al 1992); 3) isolation of bacteria that are uniquely adapted to the deep-sea environment such as barophiles (Bale, Goodman et al 1997;Barnes, Bradbrook et al 1998), and; 4) rapid activities determined by growth and radiotracer techniques (Cragg, Parkes et al 1992;Parkes, Cragg et al 1994;Patching and Eardly 1997).…”
Section: Fundamental and Applied Research On Water Generated During Pmentioning
confidence: 99%
“…In addition, other evidence exists that a high biomass of microbial life occurs deep within sediments and that these populations are active including 1) the presence of high molecular weight DNA that can be amplified using molecular techniques (Rochelle, Cragg et al 1994;Bidle, Kastner et al 1999;Li, Kato et al 1999;Vetriani, Jannasch et al 1999;Lanoil, Sassen et al 2001;LopezGarcia, LopezLopez et al 2001;Marchesi, Weightman et al 2001); 2) rapid growth of bacteria in mixed cultures (Getliff, Fry et al 1992); 3) isolation of bacteria that are uniquely adapted to the deep-sea environment such as barophiles (Bale, Goodman et al 1997;Barnes, Bradbrook et al 1998), and; 4) rapid activities determined by growth and radiotracer techniques (Cragg, Parkes et al 1992;Parkes, Cragg et al 1994;Patching and Eardly 1997). In addition, rates of bacterial processes within deep sediment samples vary vertically with mineralogical and geochemical changes, suggesting that the measured activities reflect in situ activities (Cragg, Parkes et al 1992;Parkes, Bale et al 1995). Some of these deposits are millions of years old yet still support relatively active bacterial communities (Ingebritsen, Sanford et al 2000).…”
Section: Fundamental and Applied Research On Water Generated During Pmentioning
confidence: 99%